Analysing movement behaviour and dynamic space‐use strategies among habitats using multi‐event capture‐recapture modelling. Issue 9 (13th February 2017) - Cayuela, Hugo; Pradel, Roger; Joly, Pierre; Besnard, Aurélien
Summary: The environment of most species is heterogeneous at different spatial and temporal scales; this heterogeneity can have a direct effect on various components of fitness. As a consequence, individual space‐use and movement strategies are central issues in ecology and conservation and receive considerable attention from researchers. In the last 30 years, this issue has led to the development of capture–recapture models that allow movement between sites to be quantified, while handling imperfect detection. For studies involving numerous recapture sites in which the emphasis is on dispersal or migration rather than movement between particular sites, Lagrange et al . recently proposed a parsimonious CR multi‐event model that contrasts individuals that move and individuals that stay in place, irrespective of the sites involved. In this study, we developed a generalized version of this model to allow survival probability and movement probability to differ for different types of habitat to which the individual sites may be assigned. We investigated the potential of this new parameterization by studying the movements of an amphibian, the yellow‐bellied toad ( Bombina variegata ), in a set of breeding and resting/foraging ponds. Our capture–recapture multi‐event model provides a highly flexible tool allowing users to model movements within and between several habitats. This approach can be potentially used to study movement behaviour and space‐use strategies of a wide range of taxa.